Borrelia burgdorferi is strong inducer of IFN-γ production by human primary NK cells. (July 2022) - Oosting, Marije; Brouwer, Michelle; Vrijmoeth, Hedwig D.; Pascual Domingo, Rosa; Greco, Anna; ter Hofstede, Hadewych; van den Bogaard, Ellen H.; Schalkwijk, Joost; Netea, Mihai G.; Joosten, Leo A.B.
Abstract: Natural Killer (NK) cells belong to the innate lymphoid lineage and are highly present in the human skin. NK cells can produce a range of pro-inflammatory mediators, including cytokines and chemokines. The role of NK(-T) cells in the immune response towards Borrelia burgdorferi infection was studied. The production of interleukin (IL)-6, IL-1β and interferon-gamma (IFN-γ) by human primary peripheral blood mononuclear cells (PBMCs) exposed to B. burgdorferi was assessed. Interestingly, CD56 + (NK + NK-T) cells were the only cells within the PBMC-fraction that produced IFN-γ during the first 24 h of stimulation. Within the NK(-T) cell fraction, NK cells seemed to be responsible for the IFN-γ production. Since it was previously demonstrated that both TLR2 and NOD2 receptors are involved in the recognition of B. burgdorferi, the expression of both TLR2 and NOD2 mRNA on NK cells was determined. In contrast to TLR2, NOD2 mRNA was upregulated on CD56 + (NK + NK-T) cells after Borrelia exposure. Finally, to unravel the mechanisms underlying erythema migrans (EM) development, crosstalk between CD56 + (NK + NK-T) cells and keratinocytes was investigated. CD56 + (NK + NK-T) cells activated by B. burgdorferi produced soluble mediators strongly inducing the expression of antimicrobial peptides, such as β-defensin-2 and psoriasin in human keratinocytes. In conclusion, CD56 + (NK + NK-T) cells produced IFN-γ shortly after exposure to B. burgdorferi and released soluble mediators that were able to activate keratinocytes. These observations underscore the important role of CD56 + (NK + NK-T) cells during early host defence when Borrelia burgdorferi enters the human skin during a tick bite.